Sleep quality, sleep duration and physical activity in obese adolescents: effects of exercise training. Issue 1 (2nd March 2015) - Mendelson, M.; Borowik, A.; Michallet, A.‐S.; Perrin, C.; Monneret, D.; Faure, P.; Levy, P.; Pépin, J.‐L.; Wuyam, B.; Flore, P.
Summary: Background: Decreased sleep duration and altered sleep quality are risk factors for obesity in youth. Structured exercise training has been shown to increase sleep duration and improve sleep quality. Objectives: This study aimed at evaluating the impact of exercise training for improving sleep duration, sleep quality and physical activity in obese adolescents (OB). Methods: Twenty OB (age: 14.5 ± 1.5 years; body mass index: 34.0 ± 4.7 kg m −2 ) and 20 healthy‐weight adolescents (HW) completed an overnight polysomnography and wore an accelerometer (SenseWear Bodymedia) for 7 days. OB participated in a 12‐week supervised exercise‐training programme consisting of 180 min of exercise weekly. Exercise training was a combination of aerobic exercise and resistance training. Results: Sleep duration was greater in HW compared with OB ( P  < 0.05). OB presented higher apnoea‐hypopnoea index than HW ( P  < 0.05). Physical activity (average daily metabolic equivalent of tasks [METs]) by accelerometer was lower in OB ( P  < 0.05). After exercise training, obese adolescents increased their sleep duration (+64.4 min; effect size: 0.88; P  = 0.025) and sleep efficiency (+7.6%; effect size: 0.76; P  = 0.028). Physical activity levels were increased in OB as evidenced by increased steps per day and average daily METs ( P  < 0.05). Improved sleep duration was associated with improved average daily METs (r = 0.48, P  = 0.04). Conclusion: The present study confirms altered sleep duration and quality in OB. Exercise training improves sleep duration, sleep quality and physical activity.